The Influence of Bureaucratic Leadership on Employee Performance with Work Ethic as an Intervening Variable in the Muaro Jambi Environmental Service - Meiliyani, Meiliyani; Sumarni, Sumarni; Mala, Dian (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze and describe the influence of bureaucratic leadership on employee performance with work ethic as an intervening variable in the Muaro Jambi Environmental Service. The method used is quantitative analysis with analysis techniques using SmartPls version 4.0. The sample in this study consisted of 74 employees who were selected through saturated sampling. Data collection was carried out through a questionnaire based on a likert scale and analysis using the Structural Equation Modelling (SEM) technique.